2016
DOI: 10.1016/j.neurobiolaging.2016.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Aging is associated with dimerization and inactivation of the brain-enriched tyrosine phosphatase STEP

Abstract: The striatal-enriched tyrosine phosphatase (STEP) is involved in the etiology of several age-associated neurological disorders linked to oxidative stress and is also known to play a role in neuroprotection by modulating glutamatergic transmission. However, the possible effect of aging on STEP level and activity in the brain is still unclear. In this study, using young (1 month), adult (4 month) and aged (18 month) rats we show that aging is associated with increase in dimerization and loss of activity of STEP.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 79 publications
1
15
0
Order By: Relevance
“…However, a concomitant increase in the phosphorylation of ERK MAPK, a physiological substrate of STEP, was observed in neurons treated with hydrogen peroxide, suggesting the inability of oligomerized STEP to inactivate it. Consistent with these findings, a recent study showed increased STEP dimerization and loss of STEP activity in cortex and hippocampal regions with aging (Rajagopal et al 2016). These findings suggest that STEP inactivation by oligomerization could play a role in the etiology of age-related neurodegenerative disorders by promoting chronic activation of ERK-and p38 MAPK-mediated proapoptotic pathways.…”
Section: Oligomerizationsupporting
confidence: 70%
“…However, a concomitant increase in the phosphorylation of ERK MAPK, a physiological substrate of STEP, was observed in neurons treated with hydrogen peroxide, suggesting the inability of oligomerized STEP to inactivate it. Consistent with these findings, a recent study showed increased STEP dimerization and loss of STEP activity in cortex and hippocampal regions with aging (Rajagopal et al 2016). These findings suggest that STEP inactivation by oligomerization could play a role in the etiology of age-related neurodegenerative disorders by promoting chronic activation of ERK-and p38 MAPK-mediated proapoptotic pathways.…”
Section: Oligomerizationsupporting
confidence: 70%
“…Since UPS dysfunctions can also impact the accumulation of other proteins, it cannot be excluded that decrease degradation of additional proteins might also participate in age-related cognitive impairment. This increased level of STEP during aging might also favor its dimerization and inactivation as observed in a previous study [59]. Since the functional role of these dimers is still unclear, one could argue that STEP dimerization is a protective mechanism to attenuate the deleterious effect of STEP when it accumulates during aging.…”
Section: Discussionmentioning
confidence: 51%
“…Since the functional role of these dimers is still unclear, one could argue that STEP dimerization is a protective mechanism to attenuate the deleterious effect of STEP when it accumulates during aging. Because these dimers are not found in the synaptosomal (P2) membrane fraction used here [59], further studies will be necessary to uncover the impact of STEP dimerization on memory.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, we detected an increase in STEP protein levels and a decrease of total phosphatase and STEP phosphatase activities in the retina of 20-day-old OXYS rats. These conflicting results may be associated with an age-related increase in the dimerization of STEP resulting in a substantial loss of phosphatase activity [ 31 ].…”
Section: Discussionmentioning
confidence: 99%